2021
DOI: 10.1002/jsde.12498
|View full text |Cite
|
Sign up to set email alerts
|

Iron Binding in an Ethylenediaminetetracetic Acid‐Based Gemini Surfactant Monolayer Film

Abstract: The ability of Fe3+ to bind to Langmuir monolayers of an N, N, N′, N′‐dialkyl‐N, N′‐diacetate ethylenediamine gemini surfactant has been explored. Fe3+ in the subphase resulted in the formation of compacted, liquid‐phase monolayers with a mesh‐like morphology at the micron length scale in comparison with expanded, unstructured liquid‐phase monolayers in the absence of iron. The response of the monolayer to subphase Fe3+ was different from that reported for Na+ and Ca2+ for an affiliated, shorter‐tail gemini su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We have also attempted to characterize the nanometer-scale morphology of deposited (Langmuir–Blodgett, LB) C 18 -0-C 18 monolayers. Previous attempts at the LB monolayer deposition of Ace(12)-2-Ace(12) and its longer-chain analogue onto various solid substrates have generally resulted in either poor transfer (at low surface pressures) or in the deposition of multilayer aggregates, typically with transfer ratios that were much larger than one (unpublished data; similar observations have been published for Fe 3+ -enriched subphases), likely because of the fluid nature of the films. Intriguingly, C 18 -0-C 18 films could be deposited onto glass substrates over a range of surface pressures with transfer ratios of ∼1, indicating efficient monolayer transfer.…”
Section: Resultsmentioning
confidence: 69%
“…We have also attempted to characterize the nanometer-scale morphology of deposited (Langmuir–Blodgett, LB) C 18 -0-C 18 monolayers. Previous attempts at the LB monolayer deposition of Ace(12)-2-Ace(12) and its longer-chain analogue onto various solid substrates have generally resulted in either poor transfer (at low surface pressures) or in the deposition of multilayer aggregates, typically with transfer ratios that were much larger than one (unpublished data; similar observations have been published for Fe 3+ -enriched subphases), likely because of the fluid nature of the films. Intriguingly, C 18 -0-C 18 films could be deposited onto glass substrates over a range of surface pressures with transfer ratios of ∼1, indicating efficient monolayer transfer.…”
Section: Resultsmentioning
confidence: 69%
“…We have also investigated the ion binding effects between the gemini surfactant and a number of cations at the air–water interface. , In general, results revealed a markedly weaker binding between the surfactant headgroup with divalent (Ca 2+ ) and trivalent (Fe 3+ ) ions as compared with EDTA-metal complex in the bulk, despite their similarity in molecular structures. Under AFM and BAM, clusters have been found at the surfactant monolayer in micrometer and sub-submicrometer scale, and with X-ray fluorescence technique, results suggested that the cluster found in Ace(18)-2-Ace(18)/Fe3+ systems can be attributed to complex with general formula Fe x (OH) y (3 x – y ) .…”
Section: Morphology Study Of Hydrocarbon–fluorocarbon Mixed Monolayersmentioning
confidence: 99%
“…The binding of Fe ions by a monolayer film of gemini surfactant at the water air interface was studied 50 by angle-dependent TXRF spectrometry at the liquid-surface-scattering spectrometer (NSF's ChemMatCARS) at the APS. The angle scans showed that Fe was being accumulated in a thin surface layer on top of a Fe 3+ aqueous solution.…”
Section: Grazing X-ray Techniques Including Txrf Spectrometrymentioning
confidence: 99%